ANALYSIS OF WASTE SORTING BEHAVIOR AMONG RESIDENTS OF PESANTREN PERTANIAN DARUL FALLAH BOGOR - Syari, Wirda; Fitriani, Fitriani; Asnifatima, Andi; Nauli, Humaira Anggie; Fatimah, Ratih; Aulia, Silva Aura (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Based on the results of observations and interviews with administrators, currently there has been no waste sorting carried out by residents of the Pesantren Pertanian Darul Fallah. In fact, if residents of Darul Fallah implement waste sorting behavior, the waste can be utilized as a resource that has economic value. The purpose of this study was to determine the factors related to waste sorting behavior among residents of Darul Fallah. This study is a quantitative study with a cross-sectional research design. The population were all residents of Darul Fallah with a sample size of 89 people taken using the accidental sampling method. The researcher used a questionnaire instrument which contained statements regarding knowledge, attitude, availability of facilities and waste sorting behavior. Data analysis conducted in this study included univariate and bivariate analysis using the chi square test with a significance level of 95%. Based on the results of the analysis, it is known that the attitude variable has a relationship with waste sorting behavior, while the other two variables (knowledge and availability of facilities), have no relationship with waste sorting behavior. Based on the results of the study, it is recommended that Darul Fallah carry out education regarding waste sorting followed by the implementation of regulations regarding waste sorting and the provision of the facilities needed to implement waste sorting behavior.